Desain Master Plan untuk Pengembangan Nagari Wisata dengan Pengelolaan Potensi Alam - Ningrum, Tia Ayu; Nellitawati, Nellitawati; Utama, Rizky Indra (LPPM Universitas Bumigora, 2024)
Nagari Batu Bajanjang has great natural potential for development. Nagari has beautiful views with cool air and areas producing horticultural crops, especially avocados and tomatoes. However, there have been no activities or steps taken by the inhabitants or stakeholders to achieve the Nagari Medium Term Development Plan to develop tourism in the area. For this reason, the purpose of this activity is to design a tourism development master plan for the community so that they can utilize the area more economically. The method used is conducting discussions and collaborating with the Nagari society, conducting surveys, and carrying out designs by experts. Afterward, carry out a joint evaluation with the Nagari and the Nagari community. The result of this activity was to produce a tourism master plan design for the development of the Nagari. The master plan design consists of water tourism design, children's play design, parking, prayer room, camping ground, activity hall, food court, and hot water bath. The contribution of this community service is that society can utilize the amenities to increase their income.